2004
DOI: 10.1097/00042737-200402000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Changes in aetiology and clinical outcome of acute upper gastrointestinal bleeding during the last 15 years

Abstract: The aetiology of AUGIB has changed during the last 15 years probably due to the better therapeutic approach to chronic duodenal ulcers and increasing use of NSAIDs in the elderly. Emergency surgical haemostasis has been reduced but the reduction of mortality was not significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
0
11

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 21 publications
10
68
0
11
Order By: Relevance
“…They also only identified deaths that occurred before discharge. The low mortality identified in this study (3.5%) is similar to other North American, 12 and Mediterranean studies, 5,147 but is much lower than other European studies. 3,26,61 However, a study of Medicare patients in the US found that the proportion being managed as outpatients varied between states from 18.6%-45.3%.…”
Section: Other Studiessupporting
confidence: 88%
See 1 more Smart Citation
“…They also only identified deaths that occurred before discharge. The low mortality identified in this study (3.5%) is similar to other North American, 12 and Mediterranean studies, 5,147 but is much lower than other European studies. 3,26,61 However, a study of Medicare patients in the US found that the proportion being managed as outpatients varied between states from 18.6%-45.3%.…”
Section: Other Studiessupporting
confidence: 88%
“…25 Other non variceal haemorrhage studies from Spain(n=17,663), 5 the Netherlands (n=1,720), 3 Greece (n=1,304) 147 , France (n=1,165) 61 and Italy (n=1,126), 26 did not identify reductions in non variceal inpatient mortality. Although these were large studies they may have been underpowered to detect a change, and none of them adjusted the trends in case fatality for changes in co-morbidity.…”
Section: Other Studiesmentioning
confidence: 96%
“…Additionally, more than a quarter of patients were over 80 years of age. Ten years earlier in our area this percentage was 9.8% [16] . It is clear therefore that now we have to deal with an older population with a higher risk of deterioration due to the presence of higher co-morbidities, making their management a clinical challenge.…”
Section: Discussionmentioning
confidence: 53%
“…A study comparing the causes of upper gastrointestinal bleeding among patients admitted to a hospital in Greece between 1986 and 2001 found an increase in the rate of GU (12 vs. 19%; p = 0.005) and a concomitant decrease in the rate of DU (49 vs. 33%; p < 0.0001) [16]. …”
Section: Resultsmentioning
confidence: 99%